The global labour standards controversy critical issues for developing countries - Singh, Ajit.; Zammit, Ann.; South Centre (Independent Commission of the South on Development Issues) (Geneva, Switzerland : South Centre, 2000)
Addresses the argument that trade with developing countries is the main source of the troubles afflicting large numbers of workers in the North and that low wages in developing countries give those countries an unfair competitive edge over business in the North. Does not argue against striving to achieve core or other labour standards in developing countries, but rather it aims to show that making labour standards compulsory is a deeply flawed way to achieve this goal. Attempts to clarify the analytical, empirical, and policy issues involved in the international debate on this subject and goes on to outline a constructive way forward, which would help improve labour standards both in the North and the South. This involves the promotion of a new route to global economic integration which is more helpful for labour, both in developing and advanced countries, than are the current globalization processes.
Foreword -- Overview -- Introduction: Compulsory labour standards and globalization -- Imposing labour standards on the South: The North's case -- Competition from developing countries and labour market outcomes in developed countries: An assessment -- Labour standards and economic development -- Low labour standards and competitiveness in developing countries -- On what could workers of the world unite? Economic growth and a new global economic order -- Policy implications for developing and developed countries and for international organizations.
"November 2000."
Title from web page (viewed Feb. 3, 2004).
Includes bibliographical references.
Also available in print version.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat Reader.
Keywords: Labor laws and legislation -- Developing countries; Globalization -- Economic aspects; Foreign trade and employment; Wages -- Effect of international trade on; Electronic books; Government publications